"Swimming against the Tide" Restricting Prescribing Practices in a Prison: A Personal Journey. Issue 3 (December 2015) - Craig, David Francis
ABSTRACT: Objectives: : I sought to reduce the unnecessary prescribing of psychotropic medications with abuse potential, chiefly benzodiazepines (Valium‐like drugs), HS sedatives ("sleeping pills") and psychostimulants (e.g. methylphenidate [Ritalin]) in prison settings. Method: : After each patient/inmate was assessed, benzodiazepines and HS sedatives were tapered and stopped. Patients/inmates were restricted to no more than one antidepressant and no more than one antipsychotic agent; prescriptions for psychostimulants were also restricted. Results: : Other health care staff consistently reported that the overall mental health of inmates improved soon after these changes were implemented. Prison staff reported that incidents of "strong‐arming" of inmates for medications decreased as did levels of prison violence. Prescription drug costs dropped substantially and psychiatrist visits dropped by approximately 75%. Drug‐seeking behaviors included complaints to the media, which was sympathetic, and to the College of Physicians and Surgeons of Newfoundland and Labrador, and eventually to a widely publicized peer review which, fortunately, endorsed my practices. Conclusions: : Reducing unnecessary prescribing rates of psychotropic drugs with abuse potential to prison inmates has beneficial effects on both health care costs and inmate well‐being. However, dealing with public criticism for doing so is difficult. Abstract : Objectifs: : J'ai cherché à réduire la prescription inutile de médicaments psychotropes avec un potentiel d'abus, principalement les benzodiazépines (médicaments comme le Valium), les sédatifs HS ("sleeping pills"), et les psychostimulants (ex.: méthylphénidate [Ritalin]) en milieu carcéral. Méthodologie: : Suivant l'évaluation de chaque patient/détenu, les doses de benzodiazépines et sédatifs HS étaient progressivement diminuées jusqu'à l'arrêt. Les patients/détenus étaient limités à un antidépresseur et une substance antipsychotique; les prescriptions de psychostimulants étaient aussi limitées. Résultats: : Le personnel médical signalait régulièrement que la santé mentale globale des détenus s'améliorait peu après que les changements soient mis en place. Le personnel carcéral a signalé une diminution des incidents impliquant la force avec d'autres détenus pour obtenir des médicaments et de la violence en prison. Les coûts liés à la prescription de médicaments ont diminué substantiellement et les visites en psychiatrie ont diminué d'environ 75%. Les comportements toxicomaniaques incluaient des plaintes aux médias, qui étaient favorables, et au Collège des médecins et chirurgiens de Terre‐Neuve et Labrador, puis à un examen par les pairs largement publicisé, qui ont approuvé ma pratique. Conclusions: : La diminution de prescription inutile de médicaments psychotropes avec un potentiel d'abus parmi les détenus a des effets positifs à la fois sur les coûts de soins de santé et le bien‐être des détenus. Toutefois, faire face à la critique du public pour avoir agi ainsi est difficile.